Repeatability and Reproducibility of Noninvasive Keratograph 5M Measurements in Patients with Dry Eye Disease - Sun, Xu-guang; zhang, Xiao-yu; Qu, Jing-hao; Tian, Lei (Journal of ophthalmology, 2016)
Purpose. To determine the intraexaminer repeatability and interexaminer reproducibility of tear meniscus height (TMH) and noninvasive Keratograph tear breakup time (NIKBUT) measurements obtained with the Keratograph 5M (K5M) in a sample of healthy and dry eye populations. Methods. Forty-two patients with dry eye disease (DED group) and 42 healthy subjects (healthy group) were recruited in this prospective study. In all subjects, each eye received 3 consecutive measurements using the K5M for the TMH and NIKBUTs (NIKBUT-first and NIKBUT-average). And then a different examiner repeated the measurements. The repeatability and reproducibility of measurements were assessed by the coefficient of variation (CV) and intraclass correlation coefficient (ICC). Results. The repeatability and reproducibility of TMH and NIKBUTs were good in both DED and healthy groups (CV% ≤ 26.1% and ICC ≥ 0.75 for all measurements). Patients with DED showed better intraexaminer repeatability for NIKBUTs, but worse for TMH than healthy subjects. Average TMH, NIKBUT-first, and NIKBUT-average were significantly lower in DED group than in healthy group (all P values < 0.05). Conclusions. Measurements of TMH and NIKBUTs obtained with the K5M may provide a simple, noninvasive screening test for dry eye with acceptable repeatability and reproducibility. The NIKBUTs were more reliable, but TMH was less reliable in patients with DED.